Atypical choroidal nevus in a subject with a germline PALB2 pathogenic variant - Grosel, Timothy W.; Karl, Matthew; Pilarski, Robert T.; Davidorf, Frederick H.; Abdel-Rahman, Mohamed H.; Cebulla, Colleen M. (Familial cancer, 2022)
Recent evidence suggests that PALB2 variants may increase risk for the development of uveal melanoma and uveal melanocytic neoplasms. Here we report a case of an atypical choroidal nevus in a patient with a personal history of cancer and pathogenic PALB2 germline variant. A 75-year-old white female presented with an elevated predominantly amelanotic choroidal lesion OS. On examination and ophthalmic imaging, the mass measured 8.8 mm × 6.5 mm × 1.5 mm. The mass showed predominantly medium to high reflectivity on diagnostic A-scan and acoustic hollowing on B-scan. OCT over the lesion showed no subretinal fluid. The patient has a personal history of breast cancer and gastric adenoma and a strong family history of cancer. The patient was found to have a pathogenic truncating variant in PALB2 (rs118203998 c.3549C > A, p.Y1183*). Together with our previous findings of pathogenic PALB2 variants in uveal melanoma patients, this new finding of an atypical choroidal nevus in a patient with a pathogenic PALB2 germline variant suggests that pathogenic PALB2 variants may be a risk factor for uveal melanocytic neoplasms. This finding warrants further assessment of the prevalence and progression of uveal melanocytic neoplasms in PALB2 pathogenic variant carriers.